2007
DOI: 10.1159/000101028
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Living Donor Kidney Transplantation on Markers of Cardiovascular Risk in Chronic Kidney Disease Patients

Abstract: Background: Kidney transplant (Tx) patients present a reduced cardiovascular (CV) mortality in comparison to the dialysis population, but in comparison to the general population, it is still several-fold higher. Methods: We studied risk factors for CV disease in a group of 38 patients (50% males, median age 36 years) who underwent a living donor Tx at the baseline and after 3 ± 1 and 9 ± 2 months. Results: The prevalence of overweight increased from 26 to 54% after Tx (p < 0.001). The mean systolic blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The reduction in carbonyls was previously reported in another study similar in design and population, although in that study there was no description of plasma thiol changes after transplantation. In studies performed in transplant patients, we [10] and others [11,12] have described that there was an improvement in the inflammatory status (according to the evaluation of several biomarkers, such as fibrinogen and CRP) after correction of renal function, which was dependent on the degree of renal function observed after the procedure. These observations of an improvement in inflammatory status in combination with a reduction in oxidative stress may justify the decrease in cardiovascular risk observed in transplant patients when compared to patients on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in carbonyls was previously reported in another study similar in design and population, although in that study there was no description of plasma thiol changes after transplantation. In studies performed in transplant patients, we [10] and others [11,12] have described that there was an improvement in the inflammatory status (according to the evaluation of several biomarkers, such as fibrinogen and CRP) after correction of renal function, which was dependent on the degree of renal function observed after the procedure. These observations of an improvement in inflammatory status in combination with a reduction in oxidative stress may justify the decrease in cardiovascular risk observed in transplant patients when compared to patients on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be made clear that no appropriately designed prospective randomized trial has yet shown that lowering phosphorus per se (independent from other factors) can prevent or cause regression of LVH in CKD or ESRD. Finally, renal transplant consistently reduces LVH in dialysis patients after 9 mo of post-transplant follow-up (75), suggesting that the most important determinant of the hypertrophy reduction may be the re-establishment of renal function. Closure of AVFs after transplant may also have a beneficial effect on LVH (51).…”
Section: What Is the "Natural History" Of LV Mass Change In Ckd And Ementioning
confidence: 91%
“…Larger scale studies are needed to investigate the effect of ACE inhibition on LV dimension and function and on clinical outcomes of CHF in patients with ESRD. Renal transplantation has been shown to consistently reduce LVH in dialysis patients after transplant 80, 81, 84, 85. This suggests that the most effective method of treating LVH and the associated impaired LV dysfunction is restoring renal function 80, 81…”
Section: Chf In Patients With Esrdmentioning
confidence: 99%
“…Renal transplantation has been shown to consistently reduce LVH in dialysis patients after transplant. 80,81,84,85 This suggests that the most effective method of treating LVH and the associated impaired LV dysfunction is restoring renal function. 80,81 Device Therapy for Primary Prevention of Sudden Cardiac Death Severe LV systolic dysfunction (LVEF <35%) in patients with ESRD raises a question about primary prevention of fatal cardiac arrhythmias with device therapy.…”
Section: Management Of Chf In Patients With Ckdmentioning
confidence: 99%